THE RELATIONSHIP BETWEEN JOB STRESS AND EMPLOYEES’ ALIENATION WITH MEDIATING ROLE OF ORGANIZATIONAL JUSTICE IN THE SOCIAL SECURITY ORGANIZATION IN RAZAVI KHORASAN, NORTH KHORASAN AND SOUTH KHORASAN PROVINCES - Rasti, Ali; Salajeghe, Sanjar (Revista Inclusiones, 2019)
In this study, the correlation between job stress and employees’ alienation with mediating role of organizational justice was assessed in the Social Security Organization in Razavi Khorasan, North Khorasan and South Khorasan provinces. Due to the large number of employees in the Social Security Organization, only those with a bachelor’s degree were considered as the statistical population from these provinces. Based on the structural equation modeling, the sample size was 389. The data were collected using the standard questionnaire of job stress, employees’ alienation, and organizational justice. Descriptive and analytical statistics were applied. The factors related to these variables were identified and measured. The results indicated that job stress, its four factors, alienation, its relevant factors, distributive justice, and procedural justice factors were not in desirable condition in the target population. However, organizational justice and interactional justice factor were in desirable condition. Moreover, the correlation coefficient for the relationship between job stress and alienation was positive and escalating. Any increase in the job stress factors would lead to elevated alienation. According to the negative correlation coefficients, the association of job stress factors (mental, physical, and behavioral signs) with organizational justice was in decline. The mediating effect of organizational justice on the relationship between job stress and alienation was substantiated.